USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (TICS) AS PLAY TOOLS TO MEDIATE THE LEARNING OF ELEMENTARY SCHOOL CHILDREN - II - de Oliveira Quaresma, Daniel; Semeão Prazeres, Isaque (Revista Gênero e Interdisciplinaridade, 2024)
With the arrival of information technology in schools, as a teaching tool, a new perspective of work for teachers emerges. Therefore, it is necessary to discover new, more efficient methods and techniques for working with students, awakening in them interest and pleasure in researching, organizing and transmitting their ideas, using the computer. The general objective of this study was to analyze the importance of using information and communication technologies (ICTs) as a playful tool to mediate the learning of children in elementary school II in Recife and the metropolitan region, through bibliographical and field research, with the application of questionnaire with teachers and students of elementary school II. Teachers who use technologies as a playful pedagogical resource to mediate learning report that they managed to obtain better results, because the student learns by having fun and interacting, feeling motivated when leaving the common routine in public schools: the blackboard and the whiteboard marker brush (or even chalk). ICTs facilitate communication between teacher and student, and between student and student, favoring the exchange of information and clarification of doubts about the most different contents, which facilitates student learning and consequent development, as suggested by Vygotsky’s theory. Therefore, we emphasize that it is up to the teacher to know and (re) elaborate knowledge in order to share it with the different students that make up the group. And, to acquire these skills, the teacher needs to receive training that meets the new needs of society. Hence the importance of the State directing investments towards continued training of professionals who make up its educational staff.